2020
DOI: 10.3390/diagnostics10020119
|View full text |Cite
|
Sign up to set email alerts
|

BRCAness as an Important Prognostic Marker in Patients with Triple-Negative Breast Cancer Treated with Neoadjuvant Chemotherapy: A Multicenter Retrospective Study

Abstract: Triple-negative breast cancer (TNBC) has several subtypes. The identification of markers associated with recurrence and poor prognosis in patients with TNBC is urgently needed. BRCAness is a set of traits in which BRCA1 dysfunction, arising from gene mutation, methylation, or deletion, results in DNA repair deficiency. In the current study, we evaluated the clinical significance and prognosis of BRCAness in a multicenter retrospective study. Ninety-four patients with TNBC treated with neoadjuvant chemotherapy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 35 publications
(38 reference statements)
0
3
0
Order By: Relevance
“…In TNBC, the functions of the genes are exploited to nurture tumor microenvironment and heterogeneity. BRCAness, or the trait of harbouring BRCA1/2 mutation, is deemed to be a hallmark for screening of BC or TNBC ( Kosaka et al, 2020 ). Some studies have shown that in TNBCs without BRCA1/2 mutations, TP53 seems commonly mutated, while the joint loss of p53 and BRCA1/2 activity could lead to poorer overall survival outcomes ( Kim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…In TNBC, the functions of the genes are exploited to nurture tumor microenvironment and heterogeneity. BRCAness, or the trait of harbouring BRCA1/2 mutation, is deemed to be a hallmark for screening of BC or TNBC ( Kosaka et al, 2020 ). Some studies have shown that in TNBCs without BRCA1/2 mutations, TP53 seems commonly mutated, while the joint loss of p53 and BRCA1/2 activity could lead to poorer overall survival outcomes ( Kim et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, HRD can occur in tumors that do not carry BRCA1/2 mutation, defining a subgroup of patients referred to as BRCAness. BRCAness includes a series of traits in which BRCA1 dysfunction following gene mutation, methylation, or deletion accounts for DNA repair deficiency [125]. BRCAness refers to a phenotype common in TNBC that shares molecular characteristics, and the resulting clinical features are similar to those found in BRCA-mutated patients [126].…”
Section: Biomarkers Predicting Resistance To Platinum-based Therapymentioning
confidence: 99%
“…Theoretically, detection of gene mutations associated with HR deficiency is highly recommended for diagnosing "BRCAness" and predicting the sensitivity to PARPi in TNBC. However, mutational signatures are not as stable as genomic changes but a "scar" on the genome caused by consecutive DNA damage attributable to diverse factors including previous systemic therapy, and this hinders their acuity as a marker for BRCAness (32). Consequently, fresh biopsy for HR status and functional assays for diagnosing BRCAness are necessary.…”
Section: Brcaness Molecular Traitmentioning
confidence: 99%